TEACHING STYLE AND STUDENTS' MOTIVATION IN LEARNING ENGLISH AS A FOREIGN LANGUAGE - Deastika Bayuning Sudjasmara, - (2018)
Penelitian berjudul "Teaching style and students' motivation in learning English as a foreign language" ini dilakukan di sebuah sekolah menengah atas swasta di Bandung. Penelitian ini bertujuan untuk mengidentifikasi gaya mengajar guru dan mengetahui apakah ada korelasi antara gaya mengajar tersebut dengan motivasi siswa. Mixed method research diaplikasikan dalam penelitian ini dengan melibatkan 30 siswa dan 1 orang guru. Observasi, dokumen, angket dan wawancara digunakan untuk memperoleh data penelitian. Hasilnya ditemukan bahwa gaya mengajar guru yang dominan adalah facilitator. Dalam penelitian ini kemudian diketahui juga bajwa gaya mengajar guru termasuk dalam klaster 4 dari 4 klaster gaya mengajar milik Grasha. Dalam klaster 4, gaya mengajar utamanya adalah facilitator, delegator dan expert, sementara gaya mengajar sekundernya adalah personal model dan formal authority. Terkait hubungan antara gaya mengajar dan motivasi siswa dalam mempelajari Bahasa Inggris sebagai Bahasa asing, dalam penelitian ini ditemukan bahwa ada hubungan positif yang kuat antara gaya mengajar guru dan motivasi siswa (rxy = 0.689).-----This research, titled "Teaching style and students' motivation in learning English as a foreign language", is a study conducted at a private senior high school in Bandung. It aims to identify the teacher's teaching style and investigate whether or not there is a correlation between the teaching styles and students' motivation. A mixed method was applied in this study, involving 30 students and a teacher. Observations, documents, questionnaires, and interview were employed to gain the data. The findings reveal that the dominant teaching style performed by the teacher is facilitator. It also confirms that the teacher's teaching styles in this study fall into cluster 4 category of Grasha's four cluster of teaching style. In cluster 4, the primary styles are facilitator, delegator and expert, while the secondary styles are personal model and formal authority. In response to the relationship between the teaching styles and students' motivation in learning English as a foreign language, it was found that there is a strong positive relationship between teacher's teaching styles and students' motivation (rxy = 0.689)